Adaptations neuromusculaires et métaboliques aigues lors d`un exercice de whole body vibration de faible fréquence - Theurel, J.; Rochette, L.; Borelli, G.; Dessel, S.; Fabre, J.-B. (Movement & Sport Sciences - Science & Motricité, 2013)
This study has evaluated acute physiological responses induced by low-frequencies whole body vibration (WBV). Ten participants have performed two sessions of isometric squat with WBV (2-8 Hz) and without (control: CTL) vibrations and an incremental walking exercise. The EMGRMS of vastus lateralis muscle (VL) was significantly (p < 0.01) greater during WBV (6 Hz ~ +7.0%; 8 Hz ~ +10.6%), than during the CTL session. The energy expenditure (DE) was also significantly (p < 0.01) greater during WBV ( > 4 Hz), in comparison with CTL, corresponding to that induced by an intensive walking exercise (8 Hz ~ 7.5 kcal/min). The present results evidenced the effectiveness of the low-frequencies vibrations to induce enhanced physiological responses in comparison with traditional exercises.